On the linear global stability analysis of rigid-body motion fluid–structure-interaction problems. (25th November 2020) - Negi, P. S.; Hanifi, A.; Henningson, D. S.
Abstract: Abstract : A rigorous derivation and validation for linear fluid–structure-interaction (FSI) equations for a rigid-body motion problem is performed in an Eulerian framework. We show that the 'added stiffness' terms arising in the formulation of Fanion et al. ( Revue Européenne des Éléments Finis, vol. 9, issue 6–7, 2000, pp. 681–708) vanish at the FSI interface in a first-order approximation and can be neglected when considering the growth of infinitesimal disturbances. Several numerical tests with rigid-body motion are performed to show the validity of the derived formulation by comparing the time evolution between the linear and nonlinear equations when the base flow is perturbed by identical small-amplitude perturbations. In all cases both the growth rate and angular frequency of the instability matches within 0.1 % accuracy. The derived formulation is used to investigate the phenomenon of symmetry breaking for a rotating cylinder with an attached splitter plate. The results show that the onset of symmetry breaking can be explained by the existence of a zero frequency linearly unstable mode of the coupled FSI system. Finally, the structural sensitivity of the least stable eigenvalue is studied for an oscillating cylinder, which is found to change significantly when the fluid and structural frequencies are close to resonance.